Optimal MISO UWB pre-equalizer design with spectral mask constraints - Mohsenian-Rad, Amir-Hamed; Mietzner, Jan; Schober, Robert; Wong, Vincent W. S. (2010 International ITG Workshop on Smart Antennas, WSA 2010, 2010)
In this paper, we propose a novel optimization-based pre-equalization filter (PEF) design for multiple-input single-output (MISO) direct-sequence ultra-wideband (DS-UWB) systems with pre-Rake combining. The key feature in our design is that we explicitly take into account spectral mask constraints which are usually imposed by telecommunications regulation and standardization bodies. This avoids the need for an inefficient power back-off, which is necessary for existing pre-equalizer and pre-Rake designs that are designed solely based on average transmit power constraints. Simulation results confirm that the proposed PEF design leads to significant performance gains over UWB PEF structures without any explicit spectral mask considerations. Furthermore, the use of multiple transmit antennas is shown to provide substantial combining gains compared to single-antenna transmitter structures. We also investigate the impact of certain system and optimization parameters on the performance of the proposed PEF design. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Multiple antennas; Pre-equalization; Pre-rake combining; Semi-definite programming; Spectral mask constraints; Ultra-wideband communication